SUSTAINABILITY REPORTING QUALITY IN THE BASIC MATERIALS SECTOR OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Sri Wahyuni; Mukhzarudfa Mukhzarudfa; Ratih Kusumastuti; Wiwik Tiswiyanti (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study aims to examine the quality of Environmental, Social, and Governance (ESG) reporting and its relationship with the performance and resilience of Basic Materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Based on stakeholder theory and legitimacy theory, this study analyzes the effect of ESG risk transparency on operational stability and market trust. The method used is content analysis with a priori coding based on GRI G4 indicators on 11 companies selected through purposive sampling. The results show a significant transformation in ESG risk profiles; issuers such as TINS, ANTM, SMGR, and INTP successfully achieved the lowest risk category (Negligible to Low Risk) by 2024. The findings reveal that ESG risk management has a strong linear correlation with operational efficiency and access to green financing. Conversely, companies categorized as Severe Risk are more vulnerable to regulatory pressure and market volatility. This study confirms that ESG compliance is a crucial determinant in closing the legitimacy gap and enhancing global competitiveness. The practical implications emphasize the importance of integrating green technology and transparent governance for the basic materials sector to ensure business sustainability in the low-carbon economy era. Kata kunci: Sustainability Report, ESG (Enviromental, Social, and Governance), Firm Performance.